Crystal engineering, structure–function relationships, and the future of metal–organic frameworks. Issue 2 (15th October 2014) - Allendorf, Mark D.; Stavila, Vitalie
Abstract : After twenty years of vigorous R&D, where are MOFs headed? Abstract : Metal–Organic Frameworks (MOFs) are a rapidly expanding class of hybrid organic–inorganic materials that can be rationally designed and assembled through crystal engineering. The explosion of interest in this subclass of coordination polymers results from their outstanding properties and myriad possible applications, which include traditional uses of microporous materials, such as gas storage, separations, and catalysis, as well as new realms in biomedicine, electronic devices, and information storage. The objective of this Highlight article is to provide the reader with a sense of where the field stands after roughly fifteen years of research. Remarkable progress has been made, but the barriers to practical and commercial advances are also evident. We discuss the basic elements of MOF assembly and present a conceptual hierarchy of structural elements that assists in understanding how unique properties in these materials can be achieved. Structure–function relationships are then discussed; several are now well understood, as a result of the focused efforts of many research groups over the past decade. Prospects for the use of MOFs in membranes, catalysis, biomedicine, and as active components in electronic and photonic devices are also discussed. Finally, we identify the most pressing challenges in our view that must be addressed for these materials to realize their full potential in the marketplace.